Conventional and genetic evidence on the association between adiposity and chronic kidney disease - Zhu, P; Herrington, W; Haynes, R; Emberson, J; Landray, M; Baigent, C; Lewington, S; Staplin, N (American Society of Nephrology, 2020)
Background: The size of any causal contribution of central and general adiposity to chronic kidney disease (CKD) risk and the underlying mechanism of mediation are unknown.